Enabling acceptance and use of ecological intensification options through engaging smallholder farmers in semi-arid rural Limpopo and Eastern Cape, South Africa. Issue 6 (2nd July 2020) - Rusere, Farirai; Crespo, Olivier; Dicks, Lynn; Mkuhlani, Siyabusa; Francis, Joseph; Zhou, Leocadia
ABSTRACT: Ecological intensification is being promoted to address food security and environmental challenges. It has shown the potential to improve yields as well as adapt and mitigate the effects of climate variability and change. Despite the great potential, smallholder farmers continue to shun the latter. Apart from this, limited research has been conducted focussing on their acceptance and use in smallholder sub-Saharan African agricultural systems. In this study, a qualitative approach using the Unified Theory of Acceptance and Use of Technology (UTAUT) four constructs (performance, ease of use, social influence and enablers) was used to assess behavioral intention to accept and use ecological intensification options. A total of 97 smallholder farmers from diverse farm types in rural Limpopo and Eastern Cape, South Africa participated in focus group discussions to assess behavioral intention to accept and use ecological intensification options. Smallholder farmers revealed that they were exposed to a plethora of ecological intensification options. However, acceptance and utilization of these options were low, mainly due to lack of awareness, germplasm, and technical support. The four constructs of the UTAUT framework revealed locally relevant knowledge that must be considered for effective acceptance and use of ecological intensification options. Abbreviations : ACCESS: Alliance for Collaboration for Climate and Earth System Sciences; ADCI: African Climate Development Initiative; NRF: National Research Foundation; SSA: Sub Saharan Africa; UTAUT: Unified Theory of Acceptance and Use of Technology; WRC: Water Research Commission; FAO: Food and Agriculture Organisation; CA: Conservation Agriculture